2011
DOI: 10.1371/journal.pone.0025545
|View full text |Cite
|
Sign up to set email alerts
|

Amyotrophic Lateral Sclerosis Multiprotein Biomarkers in Peripheral Blood Mononuclear Cells

Abstract: BackgroundAmyotrophic lateral sclerosis (ALS) is a fatal progressive motor neuron disease, for which there are still no diagnostic/prognostic test and therapy. Specific molecular biomarkers are urgently needed to facilitate clinical studies and speed up the development of effective treatments.Methodology/Principal FindingsWe used a two-dimensional difference in gel electrophoresis approach to identify in easily accessible clinical samples, peripheral blood mononuclear cells (PBMC), a panel of protein biomarker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
110
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 130 publications
(114 citation statements)
references
References 56 publications
4
110
0
Order By: Relevance
“…Unfortunately, using an ELISA test, we were unable to detect CRT release in the culture medium of motoneurons. Interestingly, a study aiming to identify biomarkers showed a doubling of CRT amount in ALS patients' peripheral blood mononuclear cells compared with controls (Nardo et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, using an ELISA test, we were unable to detect CRT release in the culture medium of motoneurons. Interestingly, a study aiming to identify biomarkers showed a doubling of CRT amount in ALS patients' peripheral blood mononuclear cells compared with controls (Nardo et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Page 5 of 35 Nardo et al, 2011;Noto et al, 2011;Pare et al, 2015). Only 5-10% of familial and 1% of sporadic ALS cases carry TDP-43 mutations (Lattante et al, 2012;Millecamps et al, 2010), yet wild-type TDP-43 is incorrectly processed in the majority of patients with ALS (Janssens and Van Broeckhoven, 2013).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…In ALS, the stress responsive protein Erp57 is upregulated in the spinal cord [47]. Moreover, in peripheral blood mononuclear cells of ALS patients, the level of Erp57 can be used to discriminate between patients with high and low disease severity [82]. Secondly, knock-out of calreticulin and calnexin is associated with motor impairment.…”
Section: Calreticulin and Calnexinmentioning
confidence: 99%